A cesium-formamidinium-based lead-iodine alloy perovskite active layer and its preparation method and application
By adding acetate or formate anions to coordinate with lead ions to the precursor solution of perovskite solar cells, a uniformly distributed perovskite active layer was prepared, and the perovskite battery was solved. The problem of low performance has achieved high efficiency and stability improvement.
Patent Information
- Application Number
- CN202311732251.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-16
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-12-16
AI Technical Summary
Cesium-formamidine lead-iodine perovskite solar cells are difficult to obtain high-quality uniform component perovskite active layers, resulting in lower battery performance.
Add additives with acetate or formate anions to the precursor solution to strongly coordinate with lead ions, change the crystallization kinetics process, and prepare the perovskite active layer of cesium-formamidine lead-iodine alloy by spin coating or spraying method , ensure the spatial uniform distribution of chemical components.
It improves the photoelectric conversion efficiency and operating stability of perovskite solar cells, significantly improves device performance and stability, and especially shows better long-term stability in high temperature and high humidity environments.
Smart Images

Figure CN117794334B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of perovskite solar cells, and in particular to a cesium-formamidinium-based lead-iodine alloy perovskite active layer and a preparation method and application thereof. Background Art
[0002] Solar energy is a renewable and clean energy source that is of great significance to the sustainable development of mankind. Solar cells can directly convert solar energy into electrical energy. Photoelectric conversion efficiency and preparation cost are the key factors that determine its industrial application.
[0003] Perovskite solar cells are solar cells that use perovskite-type organic-inorganic hybrid metal halide semiconductors as light-absorbing materials. Among them, the efficiency of thin-film solar cells with organic-inorganic hybrid perovskite materials (ABX3) as active layers has developed most rapidly, and its photoelectric conversion efficiency has reached nearly 26%. This is due to the high defect tolerance, long carrier transmission distance, high absorbance and many other excellent semiconductor properties of hybrid perovskite materials. This new type of thin-film solar cell has many industrial advantages such as simple production and preparation process, low cost and high performance. However, its industrialization is still facing stability problems that are difficult to solve. Among them, the outstanding problem is that the formamidinium lead iodide perovskite with the optimal band gap is unstable at room temperature and will spontaneously transform into a non-optically active phase. To stabilize this component, alloying strategies are usually required, but halogen alloying will lead to photoinduced component segregation problems, which is not conducive to stability. A-site alloying often requires the introduction of methylamine ions or methylammonium chloride auxiliary strategies for stabilization. However, methylamine small molecules have thermal stability problems and are easily decomposed under working conditions. Therefore, doping with inorganic metal rubidium and cesium ions is a more effective stabilization strategy. However, the performance of cesium-formamidine lead iodide-based perovskite solar cells is currently much lower than that of methylamine-formamidine alloy-based perovskite solar cells. This is because the solution-based preparation of cesium-formamidine-based perovskites is prone to problems such as in-plane component segregation, as well as huge differences in the crystallization properties of inorganic and organic components. Therefore, it is difficult to obtain a high-quality and uniform perovskite active layer, which makes the performance of the methylamine-free system perovskite battery low, and the third-party certified efficiency is only about 24%.
[0004] Therefore, for methylamine-free and bromine-free perovskite films, studying their crystallization process and regulating the crystallization path to obtain high-quality films with low defect density and uniform composition remains an important research direction to solve their efficiency problems. Summary of the invention
[0005] Based on this, the present invention provides a cesium-formamidinium-based lead iodine alloy perovskite active layer and a preparation method and application thereof, so as to solve the technical problem that it is difficult to obtain a high-quality uniform component perovskite active layer in the prior art cesium-formamidinium-based lead iodine-based perovskite solar cells, resulting in low battery performance.
[0006] To achieve the above object, the present invention provides a method for preparing a cesium-formamidinium-based lead-iodine alloy perovskite active layer, which comprises the following steps:
[0007] 1) dissolving iodoformamidine, cesium iodide, lead iodide, and cesium chloride in a mixed solution of dimethyl sulfoxide and N,N-dimethylformamide, and adding an additive containing anions that can strongly coordinate with lead ions according to 2-5% mol of the lead equivalent in lead iodide, shaking and dissolving, to obtain a precursor solution, wherein the additive is a formamidine compound having an acetate anion or a formate anion and / or a cesium compound having an acetate anion or a formate anion;
[0008] 2) Spin coating, scraping coating or spray coating the precursor solution obtained in step 1) to form a film, evaporate the solvent, and prepare a film having ABX 3 The active layer of cesium-formamidinium-based lead iodine alloy perovskite with a thickness of 400-900 nm, ABX 3 In the configuration, the A position is a mixture of formamidinium ions and cesium ions, the B position is a mixture of lead ions and tin ions, and the X position is a mixture of chloride ions and iodide ions.
[0009] As a further preferred technical solution of the present invention, in step 1), based on the molar percentage and the amount of iodoformamidine as the standard, the amount of cesium iodide is 5%-20%, the amount of lead iodide is 100%-120%, and the amount of cesium chloride is 1%-10%.
[0010] As a further preferred technical solution of the present invention, in step 1), the amount of iodoformamidine used is 1.4 mmol, the amount of cesium iodide used is 0.1 mmol, the amount of lead iodide used is 1.5 mmol, and the amount of cesium chloride used is 0.09 mmol.
[0011] As a further preferred technical solution of the present invention, the additive is one or a mixture of cesium acetate, formamidine acetate, cesium formate, and formamidine formate.
[0012] As a further preferred technical solution of the present invention, the additive is a mixture of cesium acetate and formamidine formate, the molar ratio of the cesium acetate to the formamidine formate is 2:1; or is a mixture of formamidine acetate and cesium formate, the molar ratio of the formamidine acetate to the cesium formate is 2:1.
[0013] As a further preferred technical solution of the present invention, the specific operation in step 2) is: the precursor solution is coated by any method of spin coating, scraping or spraying, and then annealed at 120-180° C. for 15-30 minutes. The purpose of the annealing treatment is to solidify the precursor solution into a film and eliminate the introduced anions used to coordinate with lead.
[0014] According to another aspect of the present invention, the present invention also provides a cesium-formamidinium-based lead-iodine alloy perovskite active layer, which is prepared by the above method.
[0015] According to another aspect of the present invention, the present invention also provides an application of a cesium-formamidinium-based lead-iodine alloy perovskite active layer in a perovskite solar cell.
[0016] The present invention also provides a perovskite solar cell, comprising a substrate, and a hole transport layer, an interface passivation layer, the above-mentioned cesium-formamidinium-based lead iodine alloy perovskite active layer, an electron transport layer and a metal electrode, which are sequentially arranged on the substrate.
[0017] The present invention also provides a perovskite solar cell, comprising a substrate, and an electron transport layer, the above-mentioned cesium-formamidinium-based lead iodine alloy perovskite active layer, an interface passivation layer, a hole transport layer and a metal electrode, which are sequentially arranged on the substrate.
[0018] The preparation method of the present invention comprises the following steps: firstly, dissolving iodoformamidine, cesium iodide, lead iodide and cesium chloride in a mixed solution of dimethyl sulfoxide and N,N-dimethylformamide, and adding an additive containing anions that can strongly coordinate with lead ions according to 2-5% mol of the lead equivalent in the lead iodide, and shaking and dissolving the mixture to obtain a precursor solution, wherein the additive is a formamidine compound having an acetate anion or a formate anion or / and a cesium compound having an acetate anion or a formate anion; and secondly coating the precursor solution to form a film to obtain a film having ABX 3 ABX-structured cesium-formamidinium-based lead-iodine alloy perovskite active layer 3 In the configuration, the A position is a mixture of formamidinium ions and cesium ions, the B position is a mixture of lead ions and tin ions, and the X position is a mixture of chloride ions and iodide ions. Compared with the prior art, the present invention introduces anions that can strongly coordinate with lead ions by adding additives, effectively changes the crystallization kinetics, changes the crystallization path of the system film, and obtains a cesium-formamidinium-based lead-iodine alloy perovskite active layer with uniform distribution of chemical components in space, free of methylamine and free of bromine components; moreover, the perovskite solar cell using the cesium-formamidinium-based lead-iodine alloy perovskite active layer has greatly improved its photoelectric conversion efficiency and obtained better operating stability.
[0019] The raw materials used in the method of the present invention are cheap, low in risk and widely available. Meanwhile, the reaction conditions of the present invention are mild, easy to control, simple to operate and easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0021] Figure 1 Schematic diagram of the structure of an inverted perovskite solar cell.
[0022] In the figure: 1. substrate, 2. electron transport layer, 3. cesium-formamidinium-based lead iodine alloy perovskite active layer, 4. interface passivation layer, 5. hole transport layer, 6. metal electrode.
[0023] Figure 2 The current-voltage characteristic curves of the perovskite solar cells prepared in the control example, examples 1, 2 and 3d.
[0024] Figure 3 The photoelectric conversion efficiency curves of the perovskite solar cells prepared in the control example and example three ae.
[0025] Figure 4 The stability test curves of the perovskite solar cells prepared in the control example, examples 1, 2 and 3d.
[0026] Figure 5 Fluorescence spectra of the perovskite solar cell prepared in Example 3d at different depths.
[0027] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION
[0028] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0029] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0030] The current solution method for preparing cesium-formamidine-based perovskite active layers has problems such as in-plane component segregation and huge differences in the crystallization properties of inorganic and organic components, which makes it difficult to obtain a high-quality uniform perovskite active layer, resulting in low performance of the methylamine-free perovskite battery. Moreover, in the in-situ crystallization process of the cesium-formamidine system perovskite active layer, most of them are currently directly crystallized into films in one step, but there are problems such as too fast crystallization speed leading to elemental component segregation inside the film, which seriously affects the performance and stability of the device.
[0031] In view of the above problems existing in the current solution method for preparing cesium-formamidine-based perovskite active layers, the present invention adds additives to the precursor solution to coordinate with lead ions, induces slow crystallization of the intermediate phase, and thus obtains a film with uniform components in the longitudinal and in-plane dimensions. The cations of the additives are A-site cations that already exist in the system, and no A-site ions of other impurities are introduced. Secondly, the anions are acetate ions or formate ions. Such anions have the ability to significantly reduce the potential barrier of the intermediate phase during the in-situ crystallization process through theoretical calculation simulation, thereby inducing the intermediate phase to assist crystallization, and avoiding the technical problems caused by one-step crystallization.
[0032] The precursor solution of the present invention is dissolved in a mixed solution of dimethyl sulfoxide and N, N-dimethylformamide by iodoformamidine, cesium iodide, lead iodide, and cesium chloride, and an additive is added by 2-5% mol of lead equivalent in lead iodide, and the solution is obtained by vibration. In the system, by molar percentage, and with the amount of iodoformamidine as a standard, the amount of cesium iodide is 5%-20%, the amount of lead iodide is 100%-120%, and the amount of cesium chloride is 1%-10%. In order to further improve the photoelectric conversion efficiency of perovskite solar cells, so as to obtain better operational stability, preferably, the amount of iodoformamidine is 1.4mmol, the amount of cesium iodide is 0.1mmol, the amount of lead iodide is 1.5mmol, and the amount of cesium chloride is 0.09mmol. Of course, in a specific embodiment, the specific amount of iodoformamidine, cesium iodide, lead iodide, and cesium chloride can be specifically set, without limitation.
[0033] The precursor solution of the present invention can be prepared by any conventional operation in the art to obtain a precursor solution having ABX 3 The structured cesium-formamidinium-based lead-iodine alloy perovskite active layer is as follows. For example, the precursor solution is coated into a film by any method such as spin coating, scraping or spraying, and then the solvent is evaporated and cured by heating. During the curing process, the introduced coordinated anions are removed to avoid their subsequent influence on the operation of the perovskite active layer.
[0034] In the present invention, the additive has an anion that can strongly coordinate with the lead ion, and the anion can be an acetate anion or / and a formate anion, and the cation of the additive is selected to be a formamidine ion or / and a cesium ion. The additive is preferably a mixture of cesium acetate and formamidine formate, or a mixture of cesium formate and formamidine acetate.
[0035] By applying the cesium-formamidinium-based lead-iodine alloy perovskite active layer prepared above to a perovskite solar cell, a regular structure perovskite solar cell or a trans-structure perovskite solar cell can be obtained. Of course, other configurations of perovskite solar cells can also be obtained, which are not limited here.
[0036] In the perovskite solar cell of the present application, the thickness of the cesium-formamidinium-based lead-iodine alloy perovskite active layer is generally 400-900 nm, preferably 800 nm.
[0037] Taking the regular structure perovskite solar cell as an example, its specific structure is: including a substrate, and a hole transport layer, an interface passivation layer, a cesium-formamidinium-based lead iodine alloy perovskite active layer, an electron transport layer and a metal electrode arranged on the substrate in sequence. Taking the inverted structure perovskite solar cell as an example, its specific structure is: including a substrate 1, and an electron transport layer 2, a cesium-formamidinium-based lead iodine alloy perovskite active layer 3, an interface passivation layer 4, a hole transport layer 5 and a metal electrode 6 arranged on the substrate in sequence. Its specific structure is as follows Figure 1 As shown. Among them, the substrates in the two types of perovskite solar cells (including regular structure perovskite solar cells and inverted structure perovskite solar cells) are preferably transparent conductive glass sheets or transparent conductive plastic films.
[0038] The present invention introduces anions with a size comparable to that of halogen and capable of strong coordination with lead into a precursor solution, thereby effectively regulating the crystallization path of the modified system film, obtaining a high-quality cesium-formamidinium-based lead-iodine alloy perovskite active layer (hereinafter referred to as the perovskite layer) film with uniform distribution of chemical components in space, and further preparing a methylamine-free and bromine-free perovskite solar cell device with high photoelectric conversion efficiency. By packaging the device and subjecting it to an aging environment of 60-70% humidity and 85°C, better operating stability can be obtained compared with the perovskite active layer of the methylamine-free and bromine-free system in the prior art.
[0039] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the technical solution of the present invention will be further described in detail below through specific embodiments.
[0040] Comparative Example:
[0041] Precursor solution preparation: 1.3mmol iodomethane (FAI), 0.1mmol cesium iodide (CsI), 1.5mmol lead iodide (PbI 2), 0.09 mmol cesium chloride (CsCl) was dissolved in a mixed solution of 200 μL dimethyl sulfoxide and 800 μL N,N-dimethylformamide, and the mixture was shaken and dissolved for 12 hours.
[0042] The perovskite solar cell is prepared based on the precursor solution configured as above, and the specific steps are as follows:
[0043] 1. Substrate cleaning: Using transparent conductive glass (FTO / ITO, fluorine-doped tin oxide / indium tin oxide) as the substrate, ultrasonic cleaning was performed with deionized water for 15 minutes, twice; ultrasonic cleaning was performed with ethanol for 15 minutes, twice.
[0044] 2. Electron transport layer deposition: Spin-coat tin oxide nanoparticles on a clean substrate to prepare an electron transport layer, or use chemical bath deposition to prepare the electron transport layer.
[0045] 3. Preparation of perovskite layer: Take 20 μL of the prepared precursor solution and drop it on a 2×2 cm 2 After the electron transport layer was deposited on the substrate, a spin coating process was used. The spin coating procedure was: acceleration 1000 rpm / s, accelerated to 5000 rpm for 30 seconds, 150 μL of ethyl acetate was added as an anti-solvent in the last 10 seconds of the procedure, and after the procedure was stopped, the wet film was placed on a 150°C hot stage for 20 minutes to complete annealing.
[0046] 4. Deposition of interface passivation layer: After the substrate is cooled, a quasi-two-dimensional passivation layer is coated. The specific operation is to drop 100 μL of 5 mg / ml phenylethylamine bromide isopropanol solution onto the cooled substrate where the perovskite layer has been deposited, and spin coat at 5000 rpm for 30 seconds with an acceleration of 5000 rpm / s.
[0047] 5. Preparation of hole transport layer: Dissolve 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) in 1 mL of chlorobenzene, shake and dissolve for 5 min, then add 36 μL of acetonitrile solution of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) (260 mg / mL) and 30 μL of butyl peroxide benzoyl (t-BP) solution. Spin the mixed solution at 3500 rpm on the substrate with the passivation layer deposited for 30 s to complete the preparation of the hole transport layer.
[0048] 6. Metal electrode deposition: Using vacuum evaporation, 80nm gold electrode is deposited on the substrate where the hole transport layer has been deposited to complete the preparation of the perovskite solar cell device. Its structure is as follows: Figure 1 .
[0049] The performance and stability tests of the perovskite solar cell prepared in this comparative example are as follows:
[0050] Custom perforation area is 0.064cm 2 A 0.1 mm thick metal sheet was used as a shading template, and the current-voltage characteristic curve of the perovskite solar cell device was tested under the AM 1.5G illumination provided by a 3A-level solar simulator. The results are shown in Figure 2 The stability was tested in an environmental chamber at 60% humidity and 85°C for accelerated aging. Figure 4 shown.
[0051] Embodiment 1:
[0052] Precursor solution preparation: 1.3mmol iodomethane (FAI), 0.1mmol cesium iodide (CsI), 1.5mmol lead iodide (PbI 2 ), 0.09 mmol cesium chloride (CsCl), and 0.06 mmol formamidine acetate (FAAc) were dissolved in a mixed solution of 200 μL dimethyl sulfoxide and 800 μL N,N-dimethylformamide, and the mixture was shaken and dissolved for 12 hours.
[0053] The perovskite solar cell is prepared based on the precursor solution configured as above, and the specific steps are as follows:
[0054] 1. Substrate cleaning: same as the control example;
[0055] 2. Electron transport layer deposition: same as the control example;
[0056] 3. Preparation of perovskite layer: Take 20 μL of the prepared precursor solution and add it to a 2×2 cm 2 After the electron transport layer was deposited on the substrate, a spin coating process was used. The spin coating procedure was: acceleration 1000rpm / s, accelerated to 5000rpm and spin-coated for 30s, 150μL of ethyl acetate was added as an anti-solvent in the penultimate 5s of the program, and after the program was stopped, the obtained wet film was placed on a 150℃ hot stage and heated for 20min to complete annealing. The obtained perovskite layer film was subjected to confocal fluorescence spectroscopy testing at different depths, and it was found that the emission peak positions of the film at different depths were all concentrated at 815nm and did not move, indicating that a film with uniform composition was obtained. The results are shown in the figure. Figure 5 As shown;
[0057] 4. Interface passivation layer deposition: same as the control example;
[0058] 5. Preparation of hole transport layer: same as in the control example;
[0059] 6. Metal electrode deposition: same as the control example;
[0060] The performance and stability tests of the perovskite solar cell prepared in Example 1 are as follows:
[0061] The same test method as the control example was adopted, and the current-voltage characteristic test results were as follows: Figure 2 The stability test results are shown in Figure 4 As shown, it can be seen that compared with the control example, the performance of the perovskite solar cell prepared in Example 1 is significantly improved to 26%, and the stability is also greatly improved. After aging for 1500 hours, the device efficiency retains more than 97% of the original. After adding formamidine acetate to the system, during the in-situ crystallization process, the acetate ions and lead ions are strongly coordinated, which significantly reduces the potential barrier of the intermediate phase, delays crystallization and promotes ion migration. There is no component segregation in the perovskite layer film, thereby significantly improving the device performance and stability.
[0062] Embodiment 2:
[0063] Precursor solution preparation: 1.3 mmol iodomethane (FAI), 0.1 mmol cesium iodide (CsI), 1.5 mmol lead iodide (PbI2), 0.09 mmol cesium chloride (CsCl), and 0.06 mmol cesium acetate (CsAc) were dissolved in a mixed solution of 200 μL dimethyl sulfoxide and 800 μL N, N-dimethylformamide, and shaken for 12 hours.
[0064] 1. Substrate cleaning: same as the control example;
[0065] 2. Electron transport layer deposition: same as the control example;
[0066] 3. Preparation of perovskite layer: Take 20 μL of the prepared precursor solution and drop it on a 2×2 cm 2 After the electron transport layer was deposited on the substrate, a spin coating process was used. The spin coating procedure was: acceleration 1000 rpm / s, accelerated to 5000 rpm for 30 seconds, and 150 μL of ethyl acetate was added as an anti-solvent in the penultimate 5 seconds of the procedure. After the program was stopped, the wet film was placed on a 150°C hot plate and heated for 20 minutes to complete annealing;
[0067] 4. Passivation layer deposition: same as the control example;
[0068] 5. Preparation of hole transport layer: same as in the control example;
[0069] 6. Metal electrode deposition: same as the control example;
[0070] The photoelectric conversion performance and stability test of the perovskite solar cell prepared in Example 2 are as follows:
[0071] The same test method as the control example was adopted, and the current-voltage characteristic test results were as follows: Figure 2 The stability test results are shown in Figure 4 As shown, it can be seen that compared with the control example, the performance of the perovskite solar cell prepared in Example 2 is significantly improved, and the stability is also improved, which is similar to Example 1. After 1500 hours of aging, the efficiency decay is less than 5%.
[0072] Embodiment three:
[0073] Precursor solution preparation: 1.3 mmol of iodoformamidine (FAI), 0.1 mmol of cesium iodide (CsI), 1.5 mmol of lead iodide (PbI2), 0.09 mmol of cesium chloride (CsCl), and different proportions of cesium acetate and formate according to Table 1 were dissolved in a mixed solution of 200 μL of dimethyl sulfoxide and 800 μL of N, N-dimethylformamide, and the mixture was shaken and dissolved for 12 hours.
[0074] Table 1
[0075] serial number Cesium acetate / mmol Formamidine formate / mmol Example 3a 0.01 0.05 Embodiment 3b 0.02 0.04 Example 3c 0.03 0.03 Embodiment 3d 0.04 0.02 Embodiment 3e 0.05 0.01
[0076] The perovskite solar cell is prepared based on the precursor solution configured as above, and the specific steps are as follows:
[0077] 1. Substrate cleaning: same as the control example.
[0078] 2. Electron transport layer deposition: same as the control example.
[0079] 3. Preparation of perovskite layer: Take 20 μL of the prepared precursor solution and drop it on a 2×2 cm 2 After the electron transport layer was deposited on the substrate, a spin coating process was used. The spin coating procedure was: acceleration 1000 rpm / s, accelerated to 5000 rpm for 30 seconds, 150 μL of ethyl acetate was added as an anti-solvent in the penultimate 5 seconds of the procedure, and after the procedure was stopped, the wet film was placed on a 150°C hot stage for 20 minutes to complete annealing.
[0080] 4. Passivation layer deposition: same as the control example.
[0081] 5. Preparation of hole transport layer: same as in the control example.
[0082] 6. Metal electrode deposition: same as the control example.
[0083] The photoelectric conversion performance and stability of the perovskite solar cell prepared in Example 3 were tested as follows:
[0084] The same test method as the control example was adopted, and the performance test results were as follows: Figure 2 ,3 As shown in Figures 4 and 5, it can be seen that the photoelectric performance of Examples 3ae is better than that of the control example. Among them, the performance of the perovskite solar cell prepared in Example 3d is most significantly improved compared with the control example, and its photoelectric conversion efficiency reaches 26.3%, and it has the best stability. After aging test at 85 degrees Celsius and 60% humidity for 1500 hours, the device efficiency has no obvious attenuation (such as Figure 4 The fluorescence spectra of Example 3d at different depths are shown in FIG. Figure 5 As shown, by characterizing the fluorescence spectra at different depths, the emission peak information at different depths can be obtained. The gradient band gap in depth caused by the ion segregation on the longitudinal scale is reflected in the fluorescence spectrum as the gradient displacement of the emission peak at different depths. Therefore, the present invention effectively solves the problem of cesium ion segregation on the longitudinal scale by adding strongly coordinating anions.
[0085] In Example 3ae, cesium acetate and formamidine formate are mixed in different proportions. In the system, cesium acetate and formamidine formate show a synergistic effect. The cations in the additives will also have a certain effect on the crystallization. In order to obtain the optimal crystallization state, the optimal crystallization rate control can be achieved by coordinating two different anions, and a perovskite active layer with higher crystallization quality is obtained, and finally the optimal device performance is achieved. The perovskite solar cell prepared in Example 3d has the best effect.
[0086] Comparative Example 1:
[0087] As a control experimental group of Example 1, the same method as Example 1 was adopted to prepare a precursor solution and prepare a perovskite solar cell, except that the additives used in the prepared precursor solution were different from those of the present invention, as follows:
[0088] The cations in the additive are replaced by methylamine small molecules. Due to the thermal stability problem of methylamine small molecules, the test results show that the high-temperature operating stability of the perovskite solar cell is significantly reduced. If replaced by rubidium ions, the photoelectric conversion efficiency of the device is reduced, which is far less than that of Example 1 of the present invention.
[0089] Comparative Example 2:
[0090] As a control experimental group of Example 1, the same method as Example 1 was adopted to prepare a precursor solution and prepare a perovskite solar cell, except that the additives used in the prepared precursor solution were different from those of the present invention, as follows:
[0091] After replacing the additives with anions containing large-sized coordinating anions, such as methanesulfonate and trifluoroacetate, the components in the cured perovskite film were tested and the presence of large-sized coordinating anions was found. This is because large-sized coordinating anions are difficult to remove by thermal annealing, and these substances will remain in the battery perovskite active layer, resulting in a decrease in the long-term operating stability of the device.
[0092] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.
Claims
1. A method for preparing a cesium-formamidinium-based lead-iodine alloy perovskite active layer, characterized in that: The following steps are involved: 1) dissolving iodoformamidine, cesium iodide, lead iodide and cesium chloride in a mixed solution of dimethyl sulfoxide and N,N-dimethylformamide, and adding an additive containing anions that can strongly coordinate with lead ions according to 2-5 mol% of the lead equivalent in lead iodide, shaking and dissolving, to obtain a precursor solution, wherein the additive is a formamidine compound having an acetate anion or a formate anion and / or a cesium compound having an acetate anion or a formate anion; 2) The precursor solution obtained in step 1) is coated to form a film to obtain a cesium-formamidinium-based lead-iodine alloy perovskite active layer having an ABX3 configuration, wherein the A position is a mixture of formamidinium ions and cesium ions, the B position is a lead ion, and the X position is a mixture of chloride ions and iodine ions.
2. The method for preparing the cesium-formamidinium-based lead-iodine alloy perovskite active layer according to claim 1, characterized in that: In step 1), based on the molar percentage and the amount of iodoformamidine as the standard, the amount of cesium iodide is 5%-20%, the amount of lead iodide is 100%-120%, and the amount of cesium chloride is 1%-10%.
3. The method for preparing the cesium-formamidinium-based lead-iodine alloy perovskite active layer according to claim 1, characterized in that: In step 1), the amount of iodoformamidine used is 1.4 mmol, the amount of cesium iodide used is 0.1 mmol, the amount of lead iodide used is 1.5 mmol, and the amount of cesium chloride used is 0.09 mmol.
4. The method for preparing the cesium-formamidinium-based lead-iodine alloy perovskite active layer according to claim 1, characterized in that: The additive is one of cesium acetate, formamidine acetate, cesium formate, and formamidine formate, or a mixture of several of them.
5. The method for preparing the cesium-formamidinium-based lead-iodine alloy perovskite active layer according to claim 1, characterized in that: The specific operation in step 2) is: coating the precursor solution by any of spin coating, scraper coating or spray coating, and then annealing at 120-180° C. for 15-30 min.
6. The method for preparing the cesium-formamidinium-based lead-iodine alloy perovskite active layer according to claim 1, characterized in that: In step 2), the thickness of the obtained cesium-formamidinium-based lead iodine alloy perovskite active layer is 400-900 nm.
7. A cesium-formamidinium-based lead-iodine alloy perovskite active layer, characterized in that: The preparation method is described in any one of claims 1 to 6.
8. Use of the cesium-formamidinium-based lead-iodine alloy perovskite active layer according to claim 7 in perovskite solar cells.
9. A perovskite solar cell, characterized in that: The invention comprises a substrate, and a hole transport layer, an interface passivation layer, a cesium-formamidinium-based lead iodine alloy perovskite active layer, an electron transport layer and a metal electrode which are sequentially arranged on the substrate.
10. A perovskite solar cell, characterized in that: The invention comprises a substrate, and an electron transport layer, a cesium-formamidinium-based lead iodine alloy perovskite active layer as claimed in claim 7, an interface passivation layer, a hole transport layer and a metal electrode which are sequentially arranged on the substrate.
